2022
DOI: 10.1155/2022/1682502
|View full text |Cite
|
Sign up to set email alerts
|

A Methodical Review on the Applications and Potentialities of Using Nanobiosensors for Disease Diagnosis

Abstract: Presently, with the introduction of nanotechnology, the evolutions and applications of biosensors and/or nanobiosensors are becoming prevalent in various scientific domains such as environmental and agricultural sciences as well as biomedical, clinical, and healthcare sciences. Trends in these aspects have led to the discovery of various biosensors/nanobiosensors with their tremendous benefits to mankind. The characteristics of the various biosensors/nanobiosensors are primarily based on the nature of nanomate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 154 publications
(92 reference statements)
0
11
0
Order By: Relevance
“…The environmental boosts resulting from the response to the CV-19 pandemic have now be reversed as the swift increase in economic activities began to come. As suggested by [ 27 , 40 ], if we are to sustain these environmental boosts relished during the CV-19 pandemic era, there should be a clear prominence that will promote fairness, sustainable environmental safety based on a just evolution in what identified as “green economy.”…”
Section: Ghg Emission During the Cv-19 Pandemicmentioning
confidence: 99%
See 2 more Smart Citations
“…The environmental boosts resulting from the response to the CV-19 pandemic have now be reversed as the swift increase in economic activities began to come. As suggested by [ 27 , 40 ], if we are to sustain these environmental boosts relished during the CV-19 pandemic era, there should be a clear prominence that will promote fairness, sustainable environmental safety based on a just evolution in what identified as “green economy.”…”
Section: Ghg Emission During the Cv-19 Pandemicmentioning
confidence: 99%
“…(i) Given that society resilience depends on an ecological support system with a strong resilience, the CV-19 pandemic emphasizes the connections between natural and societal organizations even more (ii) The intensification of the food system and the loss of biodiversity are contributing to the rise of zoonotic illnesses (iii) Environmental factors including air quality appear to have an impact on the effects of the CV-19 virus and are frequently tied to social disparities (iv) Unwanted effects include increased reliance on plastics alone and a decrease in gasoline prices as a result of lockdowns (v) Even though these effects are anticipated to be brief, the lockdowns during the CV-19 pandemic may have some immediate, brief positive effects on the environment, particularly in terms of GHG emission and the quality of the air 2 BioMed Research International However, it is proposed and advised that an additional study is required in order to link the detected evidence and reported environmental changes to the CV-19 virus [27]. Nevertheless, this facile but brief review study will be centered mainly on the gas flare (GF), burning of fossil fuels (BFFs) from automobile exhaust, and other industrial activities as well as other ensuing factors responsible for GHG emission during the CV-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human life safety is frequently endangered by common and infectious diseases, including cardiovascular diseases, cancer, COVID-19, Ebola, SARS, and more. [1] To tackle these challenges, efficient, advanced, and convenient immunological strategies are urgently required for the screening, diagnosis, and prognosis monitoring of diseases. [2] These approaches can enhance the quality of life and survival rates of patients while also mitigating the risk of disease outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a surge in research investigations in this sector in recent years, with several publications. Numerous studies on this topic have also been published, with specific use of nanomaterials, electrochemical signal interpretation, and aptamer identification [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%